(untitled) (Contemporary Journal of Social Science Review, 2025)
The incorporation of technology into instructional programs has become a critical component in preparing learners to thrive in the digital age. However, schools in underdeveloped regions often encounter considerable obstacles when it comes to providing sufficient technology infrastructure. This study investigated the status of computer laboratory facilities in public sector high schools of Loralai, a district in Balochistan, Pakistan. Using a descriptive survey design, data were collected from all 25 high schools through structured observation and measurement. Findings revealed that none of technological infrastructure indicator, such as computer labs, their area, seating capacity and number of functional computers fell under standards provided by national and international standards. Furthermore, none of the schools had supporting facilities such as printers or photocopiers. The study provides a baseline for local and provincial education by highlight a severe gap between the current state of technological infrastructure and international benchmarks, reflecting broader disparities in educational resources across underdeveloped provinces. Given that the study underscores the urgent need for policy interventions and targeted investments to bridge the digital divide in secondary education. Moreover, education authorities are suggested to prioritize resource allocation and align school facilities with global standards, ultimately supporting equitable digital learning opportunities for students in underserved regions.